Tamoxifen promotes white matter recovery and cognitive functions in male mice after chronic hypoperfusion. (December 2019) - Chen, Yuxue; Tian, Yeye; Tian, Hao; Huang, Qibo; Fang, Yongkang; Wang, Wei; Wan, Yue; Pan, Dengji; Xie, Minjie
Abstract: Cerebral white matter lesions (WMLs) induced by chronic cerebral hypoperfusion are one of the major components of stroke pathology and closely associated with cognitive impairment. However, the repair and related pathophysiology of white matter after brain injury remains relatively elusive and underexplored. Successful neuroregeneration is a method for the potential treatment of central nervous system (CNS) disorders. A non-steroidal estrogen receptor modulator, Tamoxifen, is an effective inhibitor of cell-swelling-activated anion channels and can mimic neuroprotective effects of estrogen in experimental ischemic stroke. However, its remains unclear whether Tamoxifen has beneficial effects in the pathological process after WMLs. In the present study, we investigated the efficacy of Tamoxifen on multiple elements of oligovascular niche of the male C57BL/6 mice brain after bilateral carotid artery stenosis (BCAS) - induced WMLs. Tamoxifen was injected intraperitoneally once daily from 1 day after BCAS until 1 day before sacrificed. Following chronic hypoperfusion, BCAS mice presented white matter demyelination, loss of axon-glia integrity, activated inflammatory response, and cognitive impairments. Tamoxifen treatment significantly facilitated functional restoration of working memory impairment in mice after white matter injury, thus indicating a translational potential for this estrogen receptor modulator given its clinical safety and applicability for WMLs, which lack of currently available treatments. Furthermore, Tamoxifen treatment reduced microglia activation and inflammatory response, favored microglial polarization toward to the M2 phenotype, enhanced oligodendrocyte precursor cells proliferation and differentiation, and promoted remyelination after chronic hypoperfusion. Together, our data indicate that Tamoxifen could alleviate white matter injury and play multiple targets protective effects following chronic hypoperfusion, which is a promising candidate for the therapeutic target for ischemic WMLs and other demyelination diseases associated cognitive impairment. Highlights: Cerebral hypoperfusion could induce demyelination, axonal loss and cognitive function impairment. Tamoxifen attenuates the degradation of white matter integrity and cognitive impairment induced by BCAS. Tamoxifen regulates microglia activation and inflammation reaction after BCAS.